Immobilization of Nannochloropsis sp Biomass by Sol-Gel Technique as Adsorbent of Metal Ion Cu(II) from Aqueous Solutions - BUHANI; SUHARSO (Asian Journal of Chemistry, 2010)
This work is related to algae biomass immobilization with sol gel technique using TEOS precursor as silica matrix to adsorb Cu(II) in aqueous solution. The data obtained showed that adsorption processes of Cu(II) are optimum at pH of 5-6, with an interaction time of 1 h. Adsorption capacity of adsorbent from Nannochloropsis sp biomass immobilized on silica through sol gel technique is 6-7 times higher than on silica gel. Adsorption capacities of Cu(II) are found to be in the range of 11.38-14.48 kJ/mol contributing as physical interaction.